Affordability of sugar-sweetened beverages and nonessential energy-dense foods after taxation, Mexico, 2010–2022 - Néstor A. Sánchez-Ortiz; Adriana Vargas Flores; Jesús E. Morales-Ríos; J. Alai Quiroz-Reyes; M. Arantxa Colchero (Revista Panamericana de Salud Pública)
Objectives. This study had two objectives: first, to estimate trends in affordability of sugar-sweetened beverages and nonessential energy-dense foods from 2010 to 2022 in Mexico, both nationally and by household income level. The second was to simulate the effects of different tax increases for these foods and beverages to observe how much their affordability would change compared with the current scenario. Methods. We used the 2010 to 2022 rounds of the Mexican National Survey of Household Income and Expenditures. The affordability ratio was estimated as the proportion of monthly income required to purchase 16 L of sugar-sweetened beverages and 2.8 kg of nonessential energy-dense foods, amounts that reflect median monthly consumption per household. Trends in the affordability ratio and its components (e.g. income and costs) are reported. Additionally, different tax increases were simulated for 2014–2022. Results. Nationally and among low-income households, the affordability of these foods and beverages did not show significant changes before and after the implementation of the taxes on these introduced in 2014. The simulation scenarios showed that a tax of 3 pesos/L for sugar-sweetened beverages and 32% for nonessential energy-dense foods would be effective in reducing affordability at all income levels. Conclusions. Current taxes are not high enough to significantly reduce the affordability of these foods and beverages. For low-income households, increases in income were greater than the increases in prices, thus sugar-sweetened beverages and nonessential energy-dense foods did not become less affordable, even after taxes were introduced in 2014. Tax rates would need to increase significantly to reduce affordability, and they should be adjusted for economic growth to compensate for increases in household income.